2009
DOI: 10.2478/s11535-009-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Ligand structure controlled allostery in cAMP-dependent protein kinase catalytic subunit

Abstract: Protein kinase A (cAMP dependent protein kinase catalytic subunit, EC 2.7.11.11) binds simultaneously ATP and a phosphorylatable peptide. These structurally dissimilar allosteric ligands influence the binding effectiveness of each other. The same situation is observed with substrate congeners, which reversibly inhibit the enzyme. In this review these allosteric effects are quantified using the interaction factor, which compares binding effectiveness of ligands with the free enzyme and the pre-loaded enzyme com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Most interestingly, this increase was again correlated with the binding effectiveness of the nucleotide and its analogues [21]. This means that both binding sites involved in the interactions with peptides and ATP (or its analogues), are involved in allosteric regulation, as was described in [21].…”
Section: A Similar Linear Interrelationship Between Thementioning
confidence: 58%
See 2 more Smart Citations
“…Most interestingly, this increase was again correlated with the binding effectiveness of the nucleotide and its analogues [21]. This means that both binding sites involved in the interactions with peptides and ATP (or its analogues), are involved in allosteric regulation, as was described in [21].…”
Section: A Similar Linear Interrelationship Between Thementioning
confidence: 58%
“…Most interestingly, this increase was again correlated with the binding effectiveness of the nucleotide and its analogues [21]. This means that both binding sites involved in the interactions with peptides and ATP (or its analogues), are involved in allosteric regulation, as was described in [21]. Therefore the pa value is correlated with pK values for both ligands and even a weakly binding ligand could cause a relatively large allosteric effect, if its partner ligand is a strong binder.…”
Section: A Similar Linear Interrelationship Between Thementioning
confidence: 66%
See 1 more Smart Citation
“…Direct evidence that allosteric interaction between ATP and the peptide substrate binding sites manifests in the catalytic subunit of cAMPdepen dent protein kinase (PKAc) was presented by Masterson et al (2008). Thereafter, the idea of allosteric regulation in PKAc was expanded by Kuznetsov and Järv (2009),…”
mentioning
confidence: 99%
“…who presented a comprehensive survey of the available ex perimental data about allosteric interactions in this enzyme. This analysis revealed that the interaction of peptide sub strates or inhibitors with PKAc is influenced by the sim ultaneous binding of ATP or its analogs and, conversely, the binding effectiveness of ATP is governed by the pres ence of peptides (Kuznetsov and Järv 2009).…”
mentioning
confidence: 99%